2017
DOI: 10.1093/ehjqcco/qcx008
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention vs. coronary artery bypass grafting for left main revascularization: an updated meta-analysis

Abstract: Aims The optimal revascularization strategy for left main coronary artery disease (LMD) remains controversial, especially with two recent randomized controlled trials showing conflicting results. We sought to address this controversy with our analysis. Methods and results Comprehensive literature search was performed. We compared percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) for LMD revascularization using standard meta-analytic techniques. A 21% higher risk of long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
2
2
1
1
Order By: Relevance
“…A possible explanation for this could be that bypassing diseased coronary arteries through graft helps protect the heart against MI, thereby improving survival [98] . The above results are concordant with a previous meta -analysis [92] .The advantage of CABG over PCI in preventing myocardial infarction was lost at our short and long-term follow-ups, which could be elucidated by losing patients to follow-up. Therefore, further research is warranted to determine whether PCI is a safe and effective alternative to CABG in terms of reducing post-operative MI rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for this could be that bypassing diseased coronary arteries through graft helps protect the heart against MI, thereby improving survival [98] . The above results are concordant with a previous meta -analysis [92] .The advantage of CABG over PCI in preventing myocardial infarction was lost at our short and long-term follow-ups, which could be elucidated by losing patients to follow-up. Therefore, further research is warranted to determine whether PCI is a safe and effective alternative to CABG in terms of reducing post-operative MI rates.…”
Section: Discussionsupporting
confidence: 92%
“…Our study rendered that there is no difference in the composite outcome of all-cause mortality between the two groups on follow-up. These findings are supported by previous meta -analysis including randomized trials [92] , [93] . Nevertheless, PCI treatment was associated with improved survival during hospital stay.This can be explained by recent advances in PCI including drug eluting stents and biodegradable stents.This finding is also corroborated by a previous meta -analysis that considered 10 randomised trials and concluded that statistics of in-hospital mortality were much higher in patients undergoing CABG with cardiogenic shock compared to PCI [94] .However, future trials should update the existing evidence.…”
Section: Discussionsupporting
confidence: 88%
“…The techniques used in this series were similar to European Bifurcation Club recommendations [ 32 ]. In this observational study, DM status was not seen to be significantly associated with worse long-term adverse events, and this finding was inconsistent with previous reports [ 35 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although heart failure with reduced EF accounts for approximately 50% of cases [ 7 , 8 ], there is no consensus about the preference to receive PCI or CABG for patients with severe CAD and reduced EF in current medical guidelines. In some studies, patients who received CABG had better overall survival compared to those who underwent PCI [ 9 , 10 ], though the others conclude that there is no significant difference in both groups [ 11 , 12 ]. In such a population, the evaluation of the ischemic area and involved vessels and the healthy collateral vessel are very important and the methods of PCI or CABG also have an impact on the outcomes [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%